Studies on Packaging of Fresh Fish - Rao, C V N; Perigrien, P A (Fishery Technology, 1964)
Studies conducted in the laboratory and field have shown that iced fish can be preserved for longer periods in fresh and edible condition in conventional bamboo baskets by providing additional insulated linings of double layer of gunny and polythene or bitumen coated kraft paper. The quality of fish is adjudged by chemical and organoleptic evaluations.